Public service delivery in Uganda: a reconsideration of grand corruption - David Mwesigwa (Goodwood Publishing, 2021)
Purpose: This review intends to ascertain and analyse available literature for the degree of corruption in the Ugandan public organisations and how they can be enhanced to get rid of corruption. Research methodology: Focussed Mapping Review and Synthesis approach were adopted to unpack corruption in public organisations. We examine obtainable literature using thematic approach. Results: The review exposes potential influence of both predisposing factors and precipitating factors in terms of socio-economic and political dimensions. Nonetheless, Public organisations in Uganda can be enhanced to get rid of corruption by enforcing a robust blend of all the three clusters of instruments of accountability; internal, legal and external. Limitations: Since the study was largely based on Uganda, its outcomes may not be generalized. Contribution: This explanatory review underscores the apathy of government machinery to rid public organisations of corruption. There is a need for politicians and policy experts to conduct additional analysis of corruption within the public sector. Keywords: Corruption, Predisposing factors, Precipitating factors, Accountability